Machiavelli and the rise of political realism - Nemenzo, Francisco 1935- (Quezon City U.P. Diliman Interactive Learning Center, 2005)
The fourth of a series of lectures under the project Exploring the Technology of Videoconferencing in Teaching Social Science II: a general education course on the social, economic and political thought.
Lecture delivered on July 27, 2005.
Executive producer, Amelia Guevara ; Associate Producer, Celia Adriano ; Director, Grace Javier Alfonso ; Co-produced by, U.P. Computer Center, U.P. Open University Media Center, Department of Electrical and Electronics Engineering, College of Engineering.
Series Lecturer: Francisco Nemenzo ; Moderator: Malaya C. Ronas.
Keywords: Machiavelli, Niccolo -- 1469-1527 -- Congresses; Machiavelli, Niccolo -- 1469-1527 -- Congresses. -- Political and social views; Realism -- Congresses